Nitric oxide biology and pathobiology - Ignarro, Louis J.; Freeman, Bruce A. (Elsevier/AP, Academic Press, an imprint of Elsevier, 2017)
Nitric Oxide: Biology and Pathobiology, Third Edition, provides information on nitric oxide, a signaling molecule of key importance for the cardiovascular system that regulates blood pressure and blood flow to different organs. With recent links to the role of nitric oxide in the expression of healthy benefits of controlled diet and aerobic exercise, and the reactions of nitric oxide that can impact cell signaling, this book provides a comprehensive resource during a time when increased research attention is being paid across the fields of pharmacology, biochemistry, cell and molecular biology, chemistry, immunology, neurobiology, immunology, nutrition sciences, drug development and the clinical management of both acute and chronic diseases.--Provided by publisher.